Using Models and Theories of Nursing Unit of the Human Being and Caring Schools in the HMA Services - Huamán Salazar, Nancy (2019)
Models and theories in nursing practice nurse oriented task that goes beyond the art and help guide activities toimprove the management of nursing care in health services. Objective: To determine the use of nursing modelsand theories of Human Being School and Caring Unit for nurses Maria Auxiliadora Hospital. Methods: Study ofapplication, descriptive and cross-sectional level, took a sample of 137 nurses, technical survey and questionnaireinstrument was used. Results: The nurse uses the models and theories in conceptualizing nursing care by 8%, 34%person, health, environment 19% and 19%. School of Human Unit use care 12%, 23% person, 8% health, 13%environment and Caring School, 4% use care, a person 55% 69% Health and 25% environment. Conclusions:The paradigm of transformation located schools and caring man, conceptions of these theories in his person,health, environment dimension are used in very low percentage for the nurse.